Comparative Genomics Identifies Putative Interspecies Mechanisms Underlying Crbn-Sall4-Linked Thalidomide Embryopathy - Kowalski, Thayne Woycinck; Caldas-Garcia, Gabriela Barreto; Gomes, Julia do Amaral; Fraga, Lucas Rosa; Schuler-Faccini, Lavínia; Recamonde-Mendoza, Mariana; Paixão-Côrtes, Vanessa Rodrigues; Vianna, Fernanda Sales Luiz (Frontiers in Genetics, 2021)
The identification of thalidomide-Cereblon induced SALL4 degradation has brought new understandings for Thalidomide Embryopathy (TE) differences across species. Some questions, however, regarding species variability, still remain. The aim of this study was to detect sequence divergences between species, affected or not by TE, and to evaluate the regulated gene co-expression in a murine model. Here, we performed a comparative analysis of proteins experimentally established as affected by thalidomide exposure, evaluating fourteen species. The comparative analysis, regarding synteny, neighborhood, and protein conservation, was performed in 42 selected genes. Differential co-expression analysis was performed, using a publicly available assay, GSE61306, which evaluated mice embryonic stem-cells (mESC) exposed to thalidomide. The comparative analyses evidenced 20 genes in the upstream neighborhood of NOS3, that are different between the species who develop, or not, the classic TE phenotype. Considering protein sequence alignments, RECQL4, SALL4, CDH5, KDR, and NOS2 proteins had the biggest number of variants reported in unaffected species. In co-expression analysis, Crbn was a gene identified as a driver of the co-expression of other genes implicated in genetic, non-teratogenic, limb reduction defects (LRD), such as Tbx5, Esco2, Recql4, and Sall4; Crbn and Sall4 were shown to have a moderate co-expression correlation, that is affected after thalidomide exposure. Hence, even though the classic TE phenotype is not identified in mice, a deregulatory Crbn-induced mechanism is suggested in this animal. Functional studies are necessary, especially evaluating the genes responsible for LRD syndromes and their interaction with thalidomide-Cereblon.